Differential Prediction for Disadvantaged Students and Schools: The Role of High School Characteristics - Preeya P. Mbekeani; Daniel Koretz (SAGE Publishing, 2024)
Validity studies of college admissions tests have found that, on average, students who are Black or Hispanic earn lower freshman grade-point averages (FGPAs) than predicted by these test scores. This differential prediction is used as a measure of bias. These studies, however, conflate student and school characteristics. The differential prediction affecting minoritized groups may arise in part because they attended high schools in which college enrollees, regardless of race, perform worse than predicted. Using data on students who graduated from New York City public high schools in 2011 and enrolled in the City University of New York, we examined this using college admissions and high school test scores. There was no differential prediction based on race/ethnicity among students within high schools when school characteristics were accounted for. Instead, overprediction of FGPA was associated with the school proportion of enrolled Black and Hispanic students. Overprediction was larger in models with high school test scores.